mRNA turnover in yeast promoted by the MATalpha1 instability element. - Caponigro, G (1996)
The decay rates of eukaryotic transcripts can be determined by sequence elements within an mRNA. One example of this phenomenon is the rapid degradation of the yeast MATalpha1 mRNA, which is promoted by a 65 nt segment of its coding region termed the MATalpha1 instability element (MIE). The MIE is also capable of destabilizing the stable PGK1 transcript. To determine how the MIE accelerates mRNA turnover we examined the mechanism of degradation of the MATalpha1 transcript. These experiments indicated that the MATalpha1 mRNA was degraded by a deadenylation-dependent decapping reaction which exposed the transcript to 5'-->3' exonucleolytic digestion. Deletion of the MIE from the MATalpha1 mRNA decreased the rate at which this mRNA was decapped. In contrast, insertion of the MIE into the PGK1 transcript caused an increase in the rate of deadenylation of the resulting chimeric mRNA. These observations suggest that the MIE promotes rapid mRNA decay by increasing the rates of deadenylation and decapping, with its primary effect on mRNA turnover depending on additional features of a given transcript. These results also strengthen the hypothesis that deadenylation-dependent decapping is a common pathway of mRNA decay in yeast and indicate that an instability element within the coding region of an mRNA can effect nucleolytic events that occur at both the 5'- and 3'-ends of an mRNA.